Ninety‐day mortality after radiotherapy for head and neck cancer: Population‐based comparison between rural and urban patients. Issue 11 (21st July 2021) - Schlijper, Roel; Bos, Siske; Hamilton, Sarah N.; Tran, Eric; Berthelet, Eric; Wu, Jonn; Olson, Robert A.
Abstract: Background: This study assesses whether 90‐day mortality differs between patients living in rural and urban areas, as lower access to supportive care services in rural areas could result in higher mortality. Methods: All patients with head and neck cancer (HNC) treated between 1998 and 2014 with radiotherapy in British Columbia were included. Patients were divided into rurality areas according to the Modified Statistics Canada (mSC) definition, which classifies a population <30 000 as rural and ≥30 000 as urban. Results: Five thousand five hundred and fifty‐four patients were included in this study, of which 68% lived in urban centers. The 90‐day mortality for rural versus urban patients were 3.0% and 3.9% ( p  = 0.09), respectively. Univariate and multivariate analyses showed no association with 90‐day mortality and rurality. Conclusion: After controlling for potentially confounding factors, we did not find a significant association between 90‐day mortality and rurality in patients who were treated with radiotherapy for HNC in British Columbia.